Persuasive impact of online media: investigating the influence of visual persuasion - Ibrahim, Nurulhuda; Kok, Wai Wong; Shiratuddin, Mohd Fairuz (2015)
In spite of the rising attention given to persuasive design, little is known about the effect of visual persuasion in the online context, specifically in the context of human-computer communication. This research describes an experiment designed to compare the effectiveness of persuasive visual design against a plain website designed with similar web design characteristics in terms of informativeness, usability and visual aesthetic. The design of the persuasive website is extended with specific visual persuasion to encourage engagement, credibility, reciprocity, commitment, liking, social proof, authority, and scarcity. Empirical evidence shows that there are significant differences in perceived satisfaction, credibility and behavioural intention between the users who surf the non-persuasive website and the users who surf the persuasive website. The result suggested that persuasive visual design could have a positive impact on users' motivation and behavioural intention. Thus, it is proposed that further investigation should be done to understand the moderation and mediation that could take effect on persuasion processes and outcomes.